Development and evaluation of a water treatment prototype based on electromagnetic induction - Gamez B., Sebastian G. (Zamorano: Escuela Agrícola Panamericana, 2023)
The average person requires at least 2.5 L of water per day to maintain a functional and stable physical health. Although this number is considered quite low, many communities face challenges in obtaining this amount of drinking water. Surface water resources are often polluted by industrial, chemical, and biological waste that pose a risk to human health. In response, there are a variety of water treatment systems with varying costs, such as ceramic filters, the use of chemical compounds, reverse osmosis, and quantum dots. There are also existing technologies that have the potential to be used as water treatment alternatives, such as electromagnetic induction and eddy currents, which generate heat from moving magnetic fields and highly conductive, non-magnetic materials. In response, a small water treatment system was designed and prototyped using electromagnetic induction to provide thermal treatment to the water. This was done through the implementation of Design Thinking methodology. The operating system of the plant was composed of three main parts: the filtration system, the thermal treatment, and the water flow control systems, which includes automation mechanisms to control the flow of water through the different stages. The performance of the prototype was evaluated by testing the rate of temperature increase of the water, resulting in a maximum temperature of 32.34 C over a two-hour period. The construction and operating costs of the prototype were also calculated, resulting in USD 265 for its construction and USD 0.5 per each operating hour. After an evaluation of the obtained results, it was determined that the constructed prototype in its current state did not meet the required performance, being an ineffective alternative for water treatment.